Growth Responses of External Hyphae of Arbuscular Mycorrhizal Fungi to Acidic Soil Conditions and their Effects on Cowpea Growth - AGUS ROHYADI (Indonesian Society for microbiology, 2008)
The effectiveness of arbuscular mycorrhizal (AM) fungi has often been attributed to growth of their external hyphae, whilst the hyphae themselves may be subjected to the effects of severe soil conditions. The growth of external hyphae of Gigaspora margarita and Glomus etunicatum and their functions in cowpea growth have been studied at low soil pH using a pot system making is possible for the hyphae to grow separately from their host’s roots. Pots had two compartments, one for roots (RC) and one for hyphae (HC). The RC was a cylindrical bag made of 30 ìm nylon mesh that retains the roots but allows the hyphae to pass through, placed centrally and surrounded by the HC. Initially, the RC was filled with 120 g of a soil/sand mixture (pH 5.3), inoculated with G. margarita, G. etunicatum or free fungal inoculants. A pre-germinated cowpea seed was grown in the compartment for two weeks before the HC was filled with 580 g of the mix in which the pH had been adjusted to 4.6, 4.9 or 5.2. Growth of the plants and of the fungal hyphae in the HC was assessed 6 weeks later. The two fungi differed in their responses to soil pH levels in their growth of external hyphae although they colonized plant roots in the same way. At pH 4.6, the hyphae of G. etunicatum grew more weakly than those of G. margarita. Increasing the pHenhanced the growth of G. etunicatum’s hyphae but reduced G. margarita’s. In relation to their external hyphal functions, G. margarita was able to improve its shoot dry weight and P uptake of cowpea plants higher than G. etunicatum. These findings highlight the ability of developing an extensive external hyphal network under adverse conditions of excessive H+ ions as an important characteristic for theeffectiveness of AM fungi in acidic soils.